Sustainable synthesis of zinc oxide nanoparticles from Persicaria lapathifolia: versatile anticancer and antibacterial applications - Sholkamy, Essam Nageh; Abdelhamid, Mohamed A. A.; Rebai, Hadjer; Sivapunniyam, Ananth; Ki, Mi-Ran; Pack, Seung Pil; Khalifa, Hazim O. (Frontiers in Molecular Biosciences, 2025)
Colorectal cancer (CRC) is one of the most common cancers in the world and one of the leading causes of cancer mortality. In this study, zinc oxide nanoparticles (PlS-ZnO NPs) were synthesized eco-friendly using an aqueous extract from the stems of Persicaria lapathifolia and their anticancer and antibacterial activities were evaluated. The PlS-ZnO NPs were prepared by a simple sol-gel combustion method and investigated by different spectroscopic and microscopic techniques. The resulting nanoparticles were of polygonal and hexagonal morphology with the average size of 21.45 nm. The PlS-ZnO NPs exhibited high cytotoxicity against human colorectal cancer cell line (HCT-116) with IC50 value of 11.31 μg/mL. Cytomorphological studies showed that these nanoparticles killed cells through both apoptosis and necrosis. Apoptotic process was accompanied by enhancement of intracellular ROS and MMP. Moreover, the PlS-ZnO NPs exhibited excellent antibacterial activity towards different pathogenic bacteria like Bacillus subtilis, Bacillus megaterium, Vibrio cholerae and Proteus vulgaris and was found to be better than the positive control amoxicillin. These results indicate that the green synthesized PlS-ZnO NPs can be considered as a potential multifunctional agent for the treatment of colorectal cancer and bacterial infections. The environmentally friendly and cost-effective synthesis of PlS-ZnO nanoparticles (NPs) utilizing P. lapathifolia enhances the potential of this nanomaterial for medical applications. This sustainable approach not only reduces environmental impact but also aligns with the increasing demand for biocompatible materials in healthcare.